Pelaksanaan Penindakan Pelanggaran Lalu Lintas Melalui Electronic Traffic Law Enforcement (ETLE) Berdasarkan Bukti Rekaman Pelanggaran Di Wilayah Hukum Polres Indragiri Hilir - Purwo Nugroho; Vivi Arfiani Siregar; Kms Novyar Satriawan F (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2025)
This study aims to analyze the implementation of traffic violation enforcement through Electronic Traffic Law Enforcement (ETLE) based on electronic recording evidence within the jurisdiction of the Indragiri Hilir Regional Police and to identify the obstacles and efforts in implementing the system. This research employed an empirical legal research method with an empirical juridical approach. Data were collected through interviews with officers of the Traffic Unit of the Indragiri Hilir Regional Police, library research, and analysis of relevant laws and regulations. The findings indicate that the implementation of ETLE has generally been carried out in accordance with Law Number 22 of 2009 concerning Road Traffic and Transportation and the Indonesian National Police's policies on electronic traffic law enforcement. However, several obstacles remain, including limited ETLE infrastructure, outdated vehicle ownership data, low public awareness in confirming electronic violations, and inadequate supporting facilities. Therefore, improving technological infrastructure, updating vehicle registration data, enhancing personnel competence, and strengthening public education are necessary to ensure that ETLE is implemented effectively, transparently, and with greater legal certainty.